The Archive and Its Fields (KULT_online, 2010)
The anthology Archivologie collects essential texts of modern archive theory. Following Jaques Derrida’s demand for a general and interdisciplinary science of archives, the anthology combines works of famous theorisers with essays on contemporary lines of thought from both theory and practice. With papers from history, philosophy, literature, media sciences and the history of art, the anthology presents a comprehensive concept of the archive. There is therefore a dynamic discourse between the ideas of the concept and the institutions of archives, which makes this anthology a valuable contribution to current archive theories.